Hubungan Tingkat Ekstraversi dan Keterlibatan Guru Dengan Keterampilan Sosial Siswa - Rahayu, Tri, Dr. Taufik Kasturi, M.Si (2017)
This research is aimed to investigate the relationship between extroversion level and teacher's involvement with student's social skill. The hypothesis of this study is that there is a relationship between extroversion level and teacher's involvement with the student's social skill. This study is a quantitative correlation approach. The sample is gained using stratified random sampling. Number of sample in this research are 155 students of Junior High School (in SMP Negeri Sukoharjo) aged 13 up to 16 years old. Data collection is done by using three scales, namely; extraversion scale, teacher's involvement, and social skill. The result of the research shows that there is a significant relation between extroversion level and teacher's involvement with students' social skill collectively. From these two independent variables, teacher's involvement is more influenced the student's social skill. The Implication of the research in education is that the importance to increase the teacher's involvement in student guidance in order to increase the student's social skill by making relationship between students and teachers and helping students to solve their learning problems.